Compensation for arbitrary divorce in Islamic Jurisprudence Fiqh, Algerian Family Law, and Legal Legislation: A comparative study - Adel, Chebab (The International tax journal, 2025)
One of the Characteristics of the Pure Islamic Sharia Law is that it achieves Justice between Disputing Parties and Seeks to Protect the Interests of all Parties, especially in the Personal Status Cases and Matters related to the Family in particular. Some Contemporary Positive Laws have Enacted Legal Provisions relating to Arbitrary Divorce. This Research Examines the Term “Arbitrary Divorce” and the Rooting of its Provisions in Islamic Sharia law through the Fatwa Jurisprudential Heritage and the New Opinions of the Contemporary Jurists. The Researcher relied on the Descriptive Approach, then the Analytical Approach, then the Comparative Approach, in his Presentation of Jurisprudential and Legal Issues and Opinions, in order to Reach the Results that the Research Yielded.